Model LEEM: Evaluating and improving the learner experience with the use of DICTs - Santos, Gabriela Corbari dos; Silva, Deivid Eive dos S.; Valentim, Natasha M. C. (Anais Estendidos do Congresso Brasileiro de Informática na Educação (CBIE); 2024: Anais Estendidos do XIII Congresso Brasileiro de Informática na EducaçãoDO - 10.5753/cbie_estendido.2024.243437, 2024)
Learner eXperience (LX) can be defined as the perceptions and performance of learners interacting with learning environments, educational products, and resources. In this master's research, we proposed a model with different forms of assessment that allow the integration of most of the LX elements. The Learner Experience Evaluation Model (LEEM) aims to evaluate and improve LX using Digital Information and Communication Technologies. LEEM consists of three evaluation stages (pre, during, and post) to monitor and record LX progress continuously. In short, it is expected that LEEM will help educators rethink their teaching strategies when they notice that learners report difficulties with the resources adopted.